Analisis Tingkat Usabilitas Aplikasi Kamus Istilah Psikologi Menggunakan Metode System Usability Scale - Sri Ernawati; Sri Huning Anwariningsih; Anniez Rachmawati Musslifah (Program Studi Teknik Industri Universitas Setia Budi, 2023)
The digital dictionary of psychological terms is used to make easier for users to search for terms related to psychology. Usability is an important factor in development of application because it can be used to measure user satisfaction. This study aims to build a digital dictionary application of psychological terms and to analyze its usability level using the System Usability Scale (SUS) method. The research used 20 psychology students as respondents. The final value of SUS is 73.5 which indicates that user acceptance (acceptability ranges) is in the acceptable category, meaning that users can accept this application. The results show that the grade scale is still C. Adjective ratings are in the Good category. The test results are positive, the average score reaches 4.3 out of a scale of 5. This indicates that there is a user's desire to use the application (Q1), acknowledges the ease of use (Q3), functions/features provided are complete (Q5), optimism that the application will be used by others (Q7), and users feel confident in using this application (Q9). The results also recommend that for further development, developers need to pay attention to aspects of technical assistance in using applications (Q4), reduce inconsistencies in applications (Q6), and users feel there is still much to learn before using applications (Q10), so digital dictionary developers must improve the design / features to increase the level of user satisfaction.